Posaconazole: a new option for invasive fungal infection management (Hematology Meeting Reports, 2009)
For most of the last 50 years, antifungal therapy has relied on amphotericin B deoxycholate. The emergence of lipid-based amphotericin B formulations rendered a significant advance in terms of reducing toxicity, although they are still associated with renal and hepatic damage. During the late 1980s fluconazole became available. It was the first antifungal drug with an excellent safety profile, but its activity spectrum is limited. A new era in antifungal therapy began in the early 2000s with the advent of a new class of antifungal drugs, the echinocandins, with a wide activity spectrum and excellent tolerability.